Frankly, I never wanted to kiss anybody! : the story of the frog prince, as told by the frog - Loewen, Nancy, 1964-; Alonso, Denis, 1986- (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2014)
Introduces the concept of point of view through the prince's retelling of the classic fairy tale "The Frog Prince" --
Keywords: Fairy tales; Humorous stories